Tris(8‐hydroxyquinoline)aluminum(III)‐Cored Molecular Cathode Interlayer: Improving Electron Mobility and Photovoltaic Efficiency of Polymer Solar Cells. Issue 11 (26th August 2018) - Li, Zuojia; Xu, Xiaopeng; Zhang, Guangjun; Deng, Min; Li, Ying; Peng, Qiang
Abstract : Tris(8‐hydroxyquinoline)aluminum(III) (Alq3 )‐cored small molecular electrolytes, Alq3 ‐F1, Alq3 ‐F2, and Alq3 ‐F3, armed with ammonium functionalized fluorene units have been successfully designed and synthesized as efficient cathode interlayers (CILs) for high‐performance fullerene and non‐fullerene polymer solar cells (F‐PSCs and NF‐PSCs). The repeating number effect of the polar group‐grafted fluorene arms is also investigated in detail on the cathode interfacial modification and the final photovoltaic performance. Increasing the amount of ammonium functionalized fluorene units will efficiently improve the interfacial dipole moment and result in lowering the work function ( W F ) of the Al cathode. On the other hand, the proportion of Alq3 segment will decrease with increasing the repeating number of the polar group‐grafted fluorene arms, which deduce the electron mobility of the target molecules. Alq3 ‐F2 shows a good balance between the above two factors, whose devices exhibit the highest power conversion efficiencies (PCEs) of 10.15% in F‐PSCs and 13.75% in NF‐PSCs. Importantly, these CIL molecules have the excellent thickness‐insensitive property enabled by the high electron mobility of the Alq3 core. The PCEs of the PSCs incorporating the Alq3 ‐containing CILs can retain about 70–80% even with a large thickness up to 50 nm. Abstract : A series of tris(8‐hydroxyquinoline)aluminum(III) (Alq3)‐cored small molecular electrolytes, Alq3‐F1, Alq3‐F2, and Alq3‐F3, armed with ammonium functionalized ﬂuorene units have been successfully designed and synthesized as efficient cathode interlayers (CILs) for high‐performance fullerene and non‐fullerene polymer solar cells (F‐PSCs and NF‐PSCs). The proportion of account of Alq3 segment will balance the conductivity and interfacial modification ability, whose devices exhibit the highest power conversion efficiencies (PCEs) of 10.15% in F‐PSCs and 13.75% in NF‐PSCs. Importantly, these CIL molecules have the excellent thickness‐insensitive property enabled by high electron mobility of the Alq3 core. The PCEs of the PSCs incorporating the Alq3‐containing CILs can retain about 70–80% even with a large thickness up to 50 nm.